L'introduction du B2i à l'école primaire : évaluer des compétences hors d'une discipline d'enseignement ? - Cédric Fluckiger; Daniel Bart (Université de Provence, 2012)
This article is based on a survey among primary school teachers whose students take the B2i examination. It intends to study, from a didactic angle, the detailed implementation of this certification process and the difficulties and tensions generated by the assessment of ICTs skills. This prescriptive framework is characterized by a lack of explicit references to computing disciplinary contents and by an understanding of ICTs as simple tools to teach other subject matters and not as teaching objects per se. We shall analyse in particular the work done by teachers to understand, interpret and sometimes break down the competencies, to judge what should be assessed and what the required level for each competency is. More generally, this research on the B2i introduction at primary school level will lead us to question the consequences of the current curriculum trends (competency-based approaches, central role of assessment, development of the non-disciplinary or trans-disciplinary "education to ...") on teaching and certification thinking and practices.